Power variability of tidal-stream energy and implications for electricity supply. (15th September 2019) - Lewis, Matt; McNaughton, James; Márquez-Dominguez, Concha; Todeschini, Grazia; Togneri, Michael; Masters, Ian; Allmark, Matthew; Stallard, Tim; Neill, Simon; Goward-Brown, Alice; Robins, Peter
Abstract: Temporal variability in renewable energy presents a major challenge for electrical grid systems. Tides are considered predictable due to their regular periodicity; however, the persistence and quality of tidal-stream generated electricity is unknown. This paper is the first study that attempts to address this knowledge gap through direct measurements of rotor-shaft power and shore-side voltage from a 1 MW, rated at grid-connection, tidal turbine (Orkney Islands, UK). Tidal asymmetry in turbulence parameters, flow speed and power variability were observed. Variability in the power at 0.5 Hz, associated with the 10-min running mean, was low (standard deviation 10–12% of rated power), with lower variability associated with higher flow speed and reduced turbulence intensity. Variability of shore-side measured voltage was well within acceptable levels (∼0.3% at 0.5 Hz). Variability in turbine power had <1% difference in energy yield calculation, even with a skewed power variability distribution. Finally, using a "t-location" distribution of observed fine-scale power variability, in combination with an idealised power curve, a synthetic power variability model reliably downscaled 30 min tidal velocity simulations to power at 0.5 Hz (R 2 = 85% and ∼14% error). Therefore, the predictability and quality of tidal-stream energy was high and may be undervalued in a future, high-penetration renewable energy, electricity grid. Highlights: Rotor-shaft power and shore-side voltage from a 1 MW tidal-stream turbine analysed. Tidal power temporal variability (sub 10-min), was considered low. Fine-scale temporal variability did not affect present resource assessment methods. Statistical model successfully downscaled broad-scale tidal resource model data. Predictability and quality of tidal-stream energy may be undervalued at present.